Bereavement care for families - Kissane, David W. (David William); Parnes, Francine (New York : Routledge, 2014)
"Grief is a family affair. When a loved one dies, the distress reverberates throughout the immediate and extended family. Family therapy has long attended to issues of loss and grief, yet not as the dominant therapeutic paradigm. Family Grief Therapy changes that: it is a practical resource for the clinician, one that draws upon the evidence supporting family approaches to bereavement care and also provides clinically oriented, strategic guidance on how to incorporate family approaches into other models"--
Family grief / David W. Kissane -- Conceptual framework for family bereavement care : strengthening resilience / Froma Walsh -- The family with chronic physical disorders : an integrative model / John Rolland -- The family with mental illness / Peter Steinglass and Tammy Schuler -- Ethical dimensions of family bereavement care / Tomer T. Levin and Marguerite S. Lederberg -- Assessing bereaved families / Talia I. Zaider -- Therapist techniques in family work / David W. Kissane and Isabelle Dumont -- Culture and grief in families / David W. Kissane, Bridgette Boucher and Francesca Del Gaudio -- An account of family therapy in bereavement : one mother's dying legacy for her family / Su Jin Kim -- Family therapy in the context of traumatic losses / Darcy Harris and Stephanie Rabenstein -- Family therapy following suicide -- Diana C. Sands and Julian L. North -- Family therapy for the unresolved grief of ambiguous loss / Pauline Boss and Carla M. Dahl -- Perinatal loss : unforeseen tragedy with on-going grief trajectories / Nicole Alston and Valerie R. Samuels -- Family bereavement care after the death of a child / Lori Wiener and Cynthia A. Gerhardt -- Care of families with children anticipating the death of a parent / Anna C. Muriel -- Family-centered approach to helping older grieving people / J. Shep Jeffreys -- Families 'at risk' of complicated bereavement / Wendy Lichtenthal and Corinne Sweeney -- The family with socioeconomic and cultural issues / Sarah Gehlert, Teresa Moro and Lailea Noel -- Future development and dissemination of models of family bereavement care / David W. Kissane and Talia I. Zaider.
Includes bibliographical references and index.
Keywords: Bereavement; Grief therapy; Family psychotherapy; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / Couples & Family; Bereavement; Family psychotherapy; Grief therapy; Bereavement; Family Therapy